Pengaruh Jumlah Lapisan Powder Coating Jotun Pada Material Ss400 terhadap Ketebalan, Kekerasan, dan Laju Korosi - Sefian Dwi; Deni Andriyansyah; Margono Margono (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2025)
This study aims to examine the effect of the number of Jotun powder coating layers on SS400 material on the thickness, hardness, and corrosion rate. Powder coating is an effective coating method to increase the corrosion resistance and hardness of metal materials. In this study, the variation of the number of powder coating layers used was 1, 2, and 3 layers. Thickness measurements were carried out using a micrometer, while hardness was measured using the Vickers test. The corrosion rate was tested using the NaCl Immersion test method. The results showed that increasing the number of powder coating layers significantly affected the thickness and hardness of SS400 material. The addition of coating layers not only increased the thickness but also strengthened the mechanical properties of the material, which was reflected in the increase in hardness value. In addition, this study also found that the more powder coating layers applied, the lower the measured corrosion rate, thus providing better protection for the material. These findings provide important insights in the selection of coating methods to improve material performance in industrial applications.